2017
DOI: 10.1021/acs.langmuir.7b00412
|View full text |Cite
|
Sign up to set email alerts
|

Grafted Polystyrene Monolayer Brush as Both Negative and Positive Tone Electron Beam Resist

Abstract: Although spin coating is the most widely used electron-beam resist coating technique in nanolithography, it cannot typically be applied for nonflat or irregular surfaces. Here, we demonstrate that monolayer polystyrene brush can be grafted on substrates and used as both positive and negative electron-beam resist, which can be applied for such unconventional surfaces. Polystyrene is a popular negative resist when using solvent developer but solvent cannot be used for grafted polystyrene brush that is firmly bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The PS-coated Zn electrode was obtained by spin-coating an omega-hydroxy-terminated polystyrene (PS) molecule brush onto the surface of pre-polished Zn foils (see the Experimental section for details), in which the hydroxyl terminals would tether with the metallic Zn substrate via a reaction with hydroxyl groups on the substrate and the release of H 2 O . The thickness of the PS brush layer is 6.7 nm, determined by fitting ellipsometry measurements (Figure d,e), which is close to the monolayer thickness for the PS brush with the same molecular weight measured previously on silicon (5.8 nm) .…”
Section: Resultsmentioning
confidence: 76%
“…The PS-coated Zn electrode was obtained by spin-coating an omega-hydroxy-terminated polystyrene (PS) molecule brush onto the surface of pre-polished Zn foils (see the Experimental section for details), in which the hydroxyl terminals would tether with the metallic Zn substrate via a reaction with hydroxyl groups on the substrate and the release of H 2 O . The thickness of the PS brush layer is 6.7 nm, determined by fitting ellipsometry measurements (Figure d,e), which is close to the monolayer thickness for the PS brush with the same molecular weight measured previously on silicon (5.8 nm) .…”
Section: Resultsmentioning
confidence: 76%
“…Researchers have developed a handful of processes to surmount patterning challenges, and an ideal solution would minimize chemical and hydrodynamic/mechanical perturbations to the delicate 3D biological structures. Float, 86 spray, 87 brush, 88 and thermally evaporative resist coating techniques 89,90 have all shown promise for patterning 3D micro-nanostructures comprised of hard condensed matter, such as atomic force microscopy cantilevers, which are held together via covalent bonds. But these methods employ perturbative processing steps, such as wet chemical developers.…”
Section: Future Prospects: Ice Lithographymentioning
confidence: 99%
“…On the contrary, it has been reported that e-resist with low-viscosity and low-surface-tension can be coated on non-planar surfaces [26] by spin coating. Besides spin coating, various other methods have been demonstrated to deposit resist films on non-planar surfaces such as spray coating [27], Langmuir-Blodgett (LB) technique [28], float coating [8], monolayer brush [29][30][31], dip coating [30,32] and ice lithography (IL) [33][34][35][36]. However, most of these methods exhibit some major issues such as non-uniformity, ultra thin-films, reproducibility and extremely low sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Well-known examples are magnetic force microscopy [8,9], tip-enhanced Raman spectroscopy [10], near-field optical focusing [11], scanning single-electron transistor microscopy [12] and scanning thermal microscopy (SThM) [13][14][15][16][17][18][19][20][21][22][23][24][25] that demand nanofabrication on 3D atomic force microscopy (AFM) probes. Recently, a considerable amount of literature has been published on EBL for creating nanostructures on irregular surfaces [26][27][28][29][30][31][32][33][34][35][36][37][38]. However, it is still very challenging to perform EBL on non-planar, 3D architectures because of the lack of uniformity and reproducibility of electron sensitive resist (e-resist) films on the substrates.…”
Section: Introductionmentioning
confidence: 99%